2014
DOI: 10.1007/s00449-014-1222-5
|View full text |Cite
|
Sign up to set email alerts
|

A review on lipase-catalyzed reactions in ultrasound-assisted systems

Abstract: The named "green chemistry" has been receiving increasing prominence due to its environmentally friendly characteristics. The use of enzymes as catalysts in processes of synthesis to replace the traditional use of chemical catalysts present as main advantage the fact of following the principles of the green chemistry. However, processes of enzymatic nature generally provide lower yields when compared to the conventional chemical processes. Therefore, in the last years, the ultrasound has been extensively used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 67 publications
0
39
1
3
Order By: Relevance
“…Many interesting works using ultrasound to enhance biodiesel conversion with reaction catalyzed by enzymes are described in the literature (Waghmare et al, 2015;Lerin et al, 2014;Awadallak et al, 2013;Batistella et al, 2012;Fiametti et al, 2012;Kumar et al, 2011). However, we have not found reports that describe the ethanolysis of Jatropha curcas oil under ultrasound irradiation.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Many interesting works using ultrasound to enhance biodiesel conversion with reaction catalyzed by enzymes are described in the literature (Waghmare et al, 2015;Lerin et al, 2014;Awadallak et al, 2013;Batistella et al, 2012;Fiametti et al, 2012;Kumar et al, 2011). However, we have not found reports that describe the ethanolysis of Jatropha curcas oil under ultrasound irradiation.…”
Section: Introductionmentioning
confidence: 84%
“…This effect has been attributed to the deposition of glycerol on the enzyme surface (Santin et al, 2014;Michelin et al, 2015). Lerin et al (2014) reported that the residual enzyme activity and the product conversion are directly dependent of the energy used (potency and frequency), exposure time (to irradiation), substrates and solvents used in the reaction. The observed decrease in FAEE production and residual activity as a function of cycle number can also be related to the denaturation (alteration) of protein structure originated from the heat-induced destruction of noncovalent interactions, i.e., the breakage of the weak ionic and hydrogen bonding that stabilizes the three dimensional structure of the enzyme (Yadav and Lathi, 2006).…”
Section: Biocatalyst Reusementioning
confidence: 99%
“…Many interesting applications have been found in enzymatic transesterification either by microwave [19][20][21][22] or ultrasound [23,24] especially with secondary alcohols [25][26][27][28][29]. Catalysts are generally significantly more active and can also be more selective [30].…”
Section: Introductionmentioning
confidence: 99%
“…The use of ultrasound at appropriated intensity can increase the enzyme activity, intensifying the process, improving mass transfer and diffusivities of enzyme/substrates [10e12]. Although is common to find studies reporting the enzymatic synthesis using supercritical fluids [13] or ultrasound [14], the literature is poor using supercritical fluids or ultrasound [6,15,16] for hydrolysis of biomass.…”
Section: Introductionmentioning
confidence: 99%